The Protestant Reformation’s challenge to religious Iconography and sacred art - Mudau, Ndidzulafhi (Hervormde teologiese studies, 2025)
For nearly a 1000 years, Christian religious iconography representing Jesus Christ, the Virgin Mary, and biblical figures functioned as vital tools for worship, devotion, and doctrinal instruction in Western Christianity. These visual representations, including illuminated manuscripts, stained-glass windows, sculptural altarpieces, and devotional paintings, served as ‘books for the uneducated’ and focal points for spiritual reflection throughout the medieval Catholic Church. The 16th-century Protestant Reformation radically contested the theological legitimacy and spiritual efficacy of religious imagery, engendering substantial disputes between traditional visual devotional practices and nascent reformer theology. This discussion highlighted concerns over the appropriate use of imagery in Christian worship, the distinction between devotion and idolatry, and the primacy of visual versus textual religious instruction. This study investigates key European locations during the Protestant Reformation (1517–1648), analysing theological texts, iconoclastic movements, and artistic production in Lutheran Germany, Calvinist Switzerland and France, Anglican England, and Counter-Reformation Catholic territories. The study delineates a range of Protestant viewpoints, from Luther’s cautious acceptance of non-worshipped biblical art to Calvin’s strict rejection of all sacred visual representations. The Protestant challenge irrevocably destroyed the medieval synthesis of artistic expression and spiritual devotion. Catholic tradition maintained and augmented its reliance on sacred iconography, but Protestant groups adopted alternative approaches prioritising verbal scripture above visual depiction. Contribution: This study illustrates how Protestant critiques of religious iconography spurred a significant cultural revolution, impacting artistic patronage, social hierarchy, and gender dynamics beyond theological discussions. The research demonstrates that iconoclastic revolutions involved complex discussions between religious convictions and practical concerns such as economic stability, governmental authority, and social order, contesting traditional interpretations that see these events merely as theological conflicts.